2014
DOI: 10.1155/2014/596723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Da‐Cheng‐Qi Decoction on the Repair of the Injured Enteric Nerve‐Interstitial Cells of Cajal‐Smooth Muscle Cells Network in Multiple Organ Dysfunction Syndrome

Abstract: Wistar rats were randomly divided into control group, multiple organ dysfunction syndrome (MODS) group, and Da-Cheng-Qi decoction (DCQD) group. The network of enteric nerves-interstitial cells of Cajal- (ICC-) smooth muscle cells (SMC) in small intestine was observed using confocal laser scanning microscopy and transmission electron microscopy. The results showed that the numbers of cholinergic/nitriergic nerves, and the deep muscular plexus of ICC (ICC-DMP) and connexin43 (Cx43) in small intestine with MODS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The restoration of normal GI transit is considered to signal patient recovery from POI following surgery. In previous studies, T-DCQT treatment has been shown to help maintain the integrity of enteric nerveinterstitial cells in the context of the Cajal-smooth muscle cell network 17 . T-DCQT is also known to increase plasma motilin 7 , and to act as an anti-in ammatory agent 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of normal GI transit is considered to signal patient recovery from POI following surgery. In previous studies, T-DCQT treatment has been shown to help maintain the integrity of enteric nerveinterstitial cells in the context of the Cajal-smooth muscle cell network 17 . T-DCQT is also known to increase plasma motilin 7 , and to act as an anti-in ammatory agent 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of normal GI transit is considered to signal patient recovery from POI following surgery. In previous studies, T-DCQT treatment has been shown to help maintain the integrity of enteric nerve-interstitial cells in the context of the Cajal-smooth muscle cell network [ 17 ]. T-DCQT is also known to increase plasma motilin [ 7 ] and to act as an anti-inflammatory agent [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Via the neuroendocrine system, the CNS will then send signals back to various target cells within the GI (e.g., ENS). ENS, ICCs, and SMCs connect to form a network structure, which is the basic functional unit of gastrointestinal motility [ 13 15 ]. We speculate that the ICCs damage is related to brain-gut interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The enteric nervous system (ENS), ICCs, and smooth muscle cells (SMCs) connect to form a network structure, which is the basic functional unit of gastrointestinal motility. Studies have shown that the amount of ICCs is abnormal or decreased in gastrointestinal motility dysfunction diseases, or the neurotransmission of the ENS-ICCs-SMC network may be decreased [ 13 15 ]. This study is seeking to identify changes in ICCs in CPS rats and the therapeutic effects of electroacupuncture (EA) at ST36.…”
Section: Introductionmentioning
confidence: 99%